Implanting Morals in The Implementation of the Distance Learning System - Ano Maryano; Slamat Sholeh (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
This research aims to describe the efforts of classroom teachers in the cultivation of noble morals through religious activities in students of class V Madrasah Ibtidaiyah Nurul Islam Jatisari District karawang. This research uses a qualitative approach that intends to understand what phenomena are experienced by the research subject. Data collection uses observation, interview, and documentation methods. The results showed that the efforts made by teachers in the cultivation of noble morals in students through religious activities in students of class V Madrasah Ibtidaiyah Nurul Islam Jatisari District karawang are through routine activities such as performing congregational dhuha prayers, congregational dhuhur prayers, tahfiz juz 30 programs, and muhadharah programs. From the everyday activities supported by the facilities and infrastructure, the cooperation of the school with the parents of students. The problem of routine activities is limited time, lack of parental attention to the development of student character, and the impact of the surrounding environment.